Sosialisasi Perbaikan Label Kemasan Pangan Pada Home Industri di Kelurahan Wonotingal, Kota Semarang - Megananda, Rafaella Chandraseta (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
The needs of human life are always increasing from time to time. The increase in the needs of human life but not matched by an increase in income can lead to inequality. Various efforts of the community in meeting their needs are carried out by establishing a home industry. The home industry that is growing in the community is engaged in the food sector. The increase in the number of home industries that are not matched by increasing public knowledge in product management causes the home industry to not develop properly. The problem that is still faced by home industry players is the use of food packaging labels that are not under BPOM standards. There are 9 standards set by BPOM regarding provisions for food packaging labels including product name, list of ingredients used, the weight of the product, name and address of the parties producing or importing, halal logo for the required product, date and production code, expiration date, distribution number permit, and the origin of certain foodstuffs. The aim of this activities to improve of food packaging labels for home industry. Activities carried out include socialization, and evaluation activities. Through the results of the questionnaire given after the socialization activity, it showed an increase in participants' interest and knowledge about the topic being presented (100%), socialization participants played an active role during the socialization activity (80%), and participants had the motivation to develop the knowledge that had been given (100%). Based on the results of the evaluation, shows that the entire series of empowerment activities went well because there was a change in the behavior pattern of the home industry owner. The growth in the number of home industries, which is balanced with the improvement in the quality of home industries, is expected to improve the community's economy